Association between herbicide contamination and reproductive effects in freshwater mussel uniandra contradens in agricultural areas, Nan province - Tongchai Thitiphuree (Chulalongkorn University, 2015)
Thesis (M.Sc.)--Chulalongkorn University, 2012